Brinquedos e brincadeiras da vovó - Pedroso, Jussara Cavalcante; Arruda, Márcia; Matos, Dulce Souza; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf